Investigating small molecules to inhibit germinal center kinase-like kinase (GLK/MAP4K3) upstream of PKCθ phosphorylation: Potential therapy to modulate T cell dependent immunity. Issue 10 (1st June 2018) - May-Dracka, Tricia L.; Arduini, Robert; Bertolotti-Ciarlet, Andrea; Bhisetti, Govinda; Brickelmaier, Margot; Cahir-McFarland, Ellen; Enyedy, Istvan; Fontenot, Jason D.; Hesson, Thomas; Little, Kevin; Lyssikatos, Joe; Marcotte, Douglas; et al.
Graphical abstract: Abstract: Germinal center kinase-like kinase (GLK, also known as MAP4K3) has been hypothesized to have an effect on key cellular activities, including inflammatory responses. GLK is required for activation of protein kinase C-θ (PKCθ) in T cells. Controlling the activity of T helper cell responses could be valuable for the treatment of autoimmune diseases. This approach circumvents previous unsuccessful approaches to target PKCθ directly. The use of structure based drug design, aided by the first crystal structure of GLK, led to the discovery of several inhibitors that demonstrate potent inhibition of GLK biochemically and in relevant cell lines.